Edge computing business model and key solutions for its landing and deployment - Yuan ZHAO; Bing XIN; Hongyuan MA; Lifeng CHEN (Dianxin kexue)
Edge computing is an innovation of network architecture and business model for operators.5G edge computing node is composed of 5G UPF and edge computing platform.It can be deployed at different levels of the network based on the demand for bandwidth,delay and local streaming.In the perspective of 5G application scenarios,depending on edge computing can meet the customer needs of differentiated vertical industries and seize the market opportunities,which is a sharp tool for operators to enter the vertical industry.The business model,billing scheme,landing deployment strategy and scheme of edge computing deployment were mainly studied,including business scenario,infrastructure,hardware system,site selection methodology,construction scheme,peripheral networking scheme,etc.